Conjugal Mayorship: The Fernandos and the Transformation of Marikina, 1992–2010 - Mendoza, Meynardo P (Archīum Ateneo, 2021)
From 1992 to 2010, during the mayoral terms of Bayani and Maria Lourdes Carlos-Fernando, Marikina underwent an extensive transformation. The husband-and-wife team transformed it from a sleepy, semi-agricultural third-class municipality into a model city and the recipient of many awards and distinctions. Aside from providing the physical infrastructure needed to lay the foundation for the city, the Fernandos also transformed the residents by promoting a culture of order and discipline, and later on introducing corporatist practices in the delivery of basic services. In the process, Marikina became sustainable from a financial and environmental standpoint. This paper argues that Marikina’s transformation can be attributed to the following: first, that the skill sets the mayors possessed matched the city’s needs at the time of their tenure; second, that Marikina’s resurgence coincided with the reforms implemented after the transition to democratic rule starting in 1986, in particular, the passage of the Local Government Code; and, third, that Marikina experienced a continuity of policies even if there were changes in leadership. The city did not suffer from what may also be termed as “cancel culture,” wherein gains made by the previous administration were negated as a result of highly polarized politics. The paper further argues that aside from agency, Marikina’s development was also conjunctural. Marikina’s success may be attributed to the confluence of interests among stakeholders; a phenomenon termed policy coalition.